A study on Knowledge on Oral Care and Prevention of Ventilator Associated Pneumonia among critical care nurses - Dr Thoudam Kheroda Devi; Mrs. Bomneichong Leivon; Dr.Vivek Hande; Dr Kiran Maribashetti; Dr.Jnanaprakash B Karanth (Journal of Medical Care Research and Review, 2024)
Background & objectives: Ventilator-associated pneumonia (VAP) is a commonest nosocomial infection globally with highest mortality. Hence, it is very essential for nurses to possess proper knowledge and follow proper procedures during care to enhance patient outcomes. Methods: A cross-sectional online survey was conducted targeting 350 critical care nurses with age group 20-45 years of age posted in critical care settings in tertiary care hospitals in India. The association between the knowledge of oral care in preventing ventilator associated pneumonia amongst critical care nurses at tertiary care hospitals with selected demographic variables was done using appropriate statistical analyses. Results: 198 (56.6%) Critical care nurses had strong knowledge scores, 130 (37.1%) had excellent knowledge scores, 20 (5.7%) had average knowledge scores, and 2 (0.6%) had low knowledge scores. Interpretation & Conclusion: This study provided the vital insight on lack of proper knowledge among nurses on role of oral care in prevention of VAP. Therefore, education of nurses on sustainable and appropriate oral care for ICU patients, and the development of a standardized and evidence-based oral care protocol are required.